2016
DOI: 10.1080/09712119.2016.1232266
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on concentrations of nutrients in four muscles of the Sudanese dromedary (Camelus dromedaries) camel

Abstract: The aim of the present study was to determine the effect of age (3-4 and 6-7 years old) on concentration of amino acids, fatty acids, minerals, vitamins and collagen in the longissimus thoraces (LT), biceps femoris, semitendinosus and semimembranosus muscles of 12 Sudanese camels. There were significant effects of age and muscle type on moisture, fat and protein contents. The LT muscle had significantly (P < .05) higher fat than other muscles. The proportion of polyunsaturated to saturated fatty acids, which r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
3
2
0
Order By: Relevance
“…As for calcium, the regional variability was limited, although statistically significant. In any case, our results are comparable to those reported by Kadim et al [ 68 ] [2499–5840 µg/g], [ 66 ] [5490 µg/g], Raiymbek et al [ 62 ] [2290 ± 670 µg/g] in Bactrian camels, [ 69 ] (176.0 ± 4.30 µg/g) and Ibrahim et al [ 52 ] (3520–4120 µg/g). The highest phosphorus in pattern M2 was not necessarily linked to exceptional high or low levels of other elements, except selenium.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As for calcium, the regional variability was limited, although statistically significant. In any case, our results are comparable to those reported by Kadim et al [ 68 ] [2499–5840 µg/g], [ 66 ] [5490 µg/g], Raiymbek et al [ 62 ] [2290 ± 670 µg/g] in Bactrian camels, [ 69 ] (176.0 ± 4.30 µg/g) and Ibrahim et al [ 52 ] (3520–4120 µg/g). The highest phosphorus in pattern M2 was not necessarily linked to exceptional high or low levels of other elements, except selenium.…”
Section: Discussionsupporting
confidence: 90%
“…With values reported in the literature between 125.6 ± 17.8 [ 65 ] and 270 [ 66 ], or with ranges of 92–466 [ 67 ] and 133–243 µg/g [ 52 ], our values were within the normal level of calcium in camel meat.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The proximate composition of fresh and cooked meat samples is presented in Table 1. Proximate composition of the raw camel meat was found to be similar to that reported previously for dromedary camel meat [23], which documents the low lipid content in camel meat. As expected, cooking decreased the moisture content while protein, ash and fat contents were increased (p<0.05).…”
Section: Effect Of Cooking Methods On Proximate Composition Of Camel ...supporting
confidence: 84%
“…Among the different cooking methods used, the highest MDA formation is observed in microwaved samples (0.87 mg/kg), while the lowest in boiled samples (0.45 mg/kg). The formation of high MDA levels during the microwave treatment has been previously reported in foal meat and silver catfish fillets [23]. Domínguez et al [4] suggested higher MDA formation in microwaved meat samples may be due to the interaction of electromagnetic waves and fat that lead to oxidation of PUFA.…”
Section: Influence Of Cooking Methods On Lipid Oxidation Of Camel Meatmentioning
confidence: 71%